Physio-biochemical, molecular characterization, and phage susceptibility of Ralstonia pseudosolanacearum associated with tomato (Solanum lycopersicum) and eggplant (Solanum melongena) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Nurdika AAH, Arwiyanto T, Sulandari S. 2022. Physio-biochemical, molecular characterization, and phage susceptibility of Ralstonia pseudosolanacearum associated with tomato (Solanum lycopersicum) and eggplant (Solanum melongena). Biodiversitas 23: 5149-5158. Ralstonia solanacearum is a plant pathogen that causes bacterial wilt diseases in various plant species. The high diversity of these bacteria strains is the basis for their grouping into the R. solanacearum species complex (RSSC). RSSC associated with tomato and eggplant in Indonesia are commonly known as R. solanacearum. It is necessary to characterize R. solanacearum which infects tomatoes and eggplant according to the latest classification. The high diversity of strains also affects their susceptibility to bacteriophages as host-specific biocontrol agents. This research was conducted by characterizing R. solanacearum isolates from different locations based on their physio-biochemical properties, biovar, virulence, phylotype, sequevar, and susceptibility to 12 bacteriophage isolates. The phylotype identification was carried out using multiplex polymerase chain reaction with several specific primers for R. solanacearum. Amplification and sequencing based on the egl gene region were carried out to determine the sequevar of R. solanacearum isolates. As a result, isolates RS18, RS19, RS23, and RS24 had morphological, physio-biochemical, and biovar characteristics according to Ralstonia pseudosolanacearum phylotype I, biovar 3. The two most virulent isolates, RS19 and RS24 were identified as sequevar 14. RS19 and RS24 isolates were susceptible to 7 of the 12 bacteriophage isolates used in this study. Variations of bacteriophage isolates resulted in different plaque morphology which could be attributed to R. pseudosolanacearum susceptibility and bacteriophage virulence.
Keywords: Bacteriophage; Ralstonia pseudosolanacearum; Ralstonia solanacearum species complex; Solanum lycopersicum; Solanum melongena